Scholarly Pathway: Understanding, Planning, and Competency Mapping in Pharmacy Education - Gillani, Syed Wasif (J Res Pharm Pract, 2020)
Pharmaceutical education has extensive integration of courses from life sciences to technology application and drug discovery to clinical trials. Pharmacy students are capable of diverse career selection due to acquired competencies during professional education. However, there is always a lack of real-time research exposure to pharmacy students at the undergraduate level. Therefore, the purpose is to design an effective research series that provides first-hand research experience to pharmacy students during 2–4 years of PharmD studies. The course design and delivery focused on three elements, namely, quality assurance, curriculum requirement, and assessment method. The outcomes of the course series are consistent with the emerging research skills and evidence-based practitioner role. The series and multilevel of course sequels comprising from knowledge – comprehension – argument – to – synthesis of research article. Students are expected to conduct independent research project under the supervision of college faculty. This will help them to develop and advance research skills for lifelong learning. The scholarly pathway series will develop critical appraisal skills to argue/support/value the literature and develop competency for evidence-based medicines. It will be highly beneficial to develop critical thinking, professionalism, and research skills among pharmacy students.